Utilization of Papain Extracted from Chaya and Papaya Stalks as Halal Beef Tenderiser - Phothiwicha, Aekkalak; Thamsaad, Kiatisak; Boontranurak, Kanjapach; Sintuya, Panlop; Panyoyai, Naksit (Indonesian Food Science and Technology Journal, 2021)
Papain is a proteolytic enzyme extracted from plant latex. The protease has widely used in the meat industry and culinary work for a pre-tenderization step prior to further meat processing. The objective of this research was to evaluate the bioactivity of papain extracted from Chaya and papaya. The different levels of papain, casein substrate, temperature, and pH were set up in vitro conditions. Then, the fresh papain was used to digest raw beef and the beef was dried under solar process. The sun-dried beef was further analyzed of yield, moisture content, water activity, and tensile force. It was found that proteolytic activity from both plants was accelerated by a high level of papain or casein up to 2.0 (w/v). The best optimal proteolytic activity was recorded at 60oC and pH5. Later, the tenderized beef at pH6.5 was dried by a solar dryer, where an inside tunnel temperature was approximately 40oC, 40% relative humidity, and 187 Btu/ft2. hr solar radiation. The sun-dried beef had a 75% yield, a 32% moisture content, and 0.90 Aw. Despite the fact that the drying temperature and pH of beef were not optimal as given from the previous results, the tensile force and the work of tension of papain-treated beef both moist and dried states were lower than the non-treated beef.